Socialization of SAK EMKM as an Effort to Motivate Entrepreneurs and Improve the Quality of Financial Reports - Gista Rismayani; Ulfa Luthfia Nanda; Laras Pratiwi (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The difficulty of business actors in carrying out financial records is the background for the issuance of SAK EMKM. Several businesses that have been running, it was found that business actors did not keep financial records properly. Sometimes, cash outflows and cash inflows are not recorded, so there is no control over cash flows. This community service aims to socialize SAK EMKM in increasing knowledge of accounting records to business actors in Buninagara, Cipedes. This community service is in the form of socialization with the lecture method, question and answer, and discussion of micro business actors. The results show that business actors have begun to recognize and realize the importance of carrying out financial records, especially according to the Financial Standards for Micro, Small and Medium Entities (SAK EMKM), 22% of participants have understood financial records according to Financial Accounting Standards.